Pengembangan Asesmen Berbasis HOTS Menggunakan Quizizz pada Mata Pelajaran Informatika Kelas X - Amelia, Kiki; Rahmi, Ulfia; Novrianti, Novrianti; Ramayanti, Elsa (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Higher Order Thinking Skills (HOTS) is a learning assessment activity that trains students' higher order thinking skills. This is because there are no questions specifically designed to train students' higher-level thinking and the questions used by teachers in learning assessment activities are still in the types of remembering (C1), understanding (C2), and applying (C3) questions. This research aims to develop high-level thinking ability test questions that meet the requirements of question validity, reliability, and question accuracy. This type of research is Research and Development (R&D) which uses the ADDIE model with five stages, namely analysis, planning, development, and evaluation. The subject of this study is a student of class X of MAS Islamiyah Tamiang. The instruments used in this study are questionnaire response and interview instruments. The data analysis techniques used are construct validity, reliability, and practicality tests. Based on the results of the analysis obtained at the implementation stage, test questions were produced in accordance with the criteria that had been set, namely meeting valid, reliable and practical criteria used to find out the results of students' abilities during learning activities, judging from the results of the validity test categorized as valid categories. The reliability test results have a value of 0.863 including with a very high category, an average difficulty test result of 0.65 whose difficulty level has good quality and an average discriminating power test result of 0.58 with good ability and a practicality test of 82% with a very practical category